Hydrothermal Dynamics and Surface Energy Allocation in Subtropical Grasslands - WANG Heng; ZHANG Qingtao; WANG Zhiqiang; WU Xinyu (Renmin Zhujiang)
Soil hydrothermal changes are an important part of the study of eco-hydrological processes,and studies on soil hydrothermal changes in grasslands in subtropical coastal areas are relatively insufficient.This paper studied the soil hydrothermal changes and surface energy balance of grassland in a subtropical campus area by using field observation data.The results showed that:① Grassland soil moisture is affected differently by rainfall in the wet and dry seasons,with rainfall causing greater soil moisture changes in the dry season than in the wet season.On 20 December,the daily rainfall was 15.2 mm,and the soil moisture change was 0.12 m3/m3 during the study period.On 1 May,the daily rainfall was 120.3 mm,and the soil moisture change was only 0.11 m3/m3.② In terms of vertical variation in soil water potential gradient,the zero-pass surface of the soil water potential gradient occurs within 10~30 cm in the wet season and around 50 cm in the dry season.③ According to the response of soil moisture to rainfall,soil moisture transport after rainfall in the dry and wet seasons mainly occurs at a soil depth of 0~40 cm.④ The change in soil temperature is greatly influenced by seasonal temperature,and the surface soil temperature gradient is large.In spring and summer,soil temperature decreases with increasing soil depth;in autumn and winter,soil temperature increases with increasing soil depth.⑤ Within two adjacent months,transpiration from grasses is significantly reduced in the wet season relative to the dry season.In terms of energy allocation,although the wet season sees more rainfall and less energy flux,the proportion of latent heat flux is higher,with the proportion of latent heat flux between 0:00 and 6:00 and between 7:00 and 17:00 increasing by 3% and 7% respectively compared with the dry season.This paper examines rainfall and seasonal differences in the hydrothermal dynamics and surface energy of subtropical grasslands,providing information for the study of ecosystems in subtropical coastal zones.